2022
DOI: 10.1155/2022/4047572
|View full text |Cite
|
Sign up to set email alerts
|

Spatial‐Temporal Evolution and Influencing Factors of Urban Green Innovation Efficiency in China

Abstract: Promoting green urban development has become a common consensus to address environmental pollution and ecological damage, but we know little about the measurement and drivers of urban green innovation efficiency (GIE). In this article, firstly, we established a framework for assessing urban green innovation efficiency through multidimensional data, then used the spatial econometric model to reveal the spatiotemporal evolutionary characteristics of urban GIE, and, finally, analyzed the influencing factors and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…‘IS’ should attract the attention of all supply chain financial enterprises, and the level of ‘IS’ should be continuously improved. Figure 1 shows the main features and functions of supply chain IS (Lu et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…‘IS’ should attract the attention of all supply chain financial enterprises, and the level of ‘IS’ should be continuously improved. Figure 1 shows the main features and functions of supply chain IS (Lu et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the measured regional green development performance or green development level, scholars have also carried out deeper research. One avenue is the spatial differentiation of regional green development [37,38], and the other is the factors that affect the level of regional green development and their spatial spillover effects [11][12][13][14][15]39]. For example, Zhao et al [37] found that the green innovation efficiency in eastern, central, and western China is basically on the rise, but that there are differences in the upward trend, and this is based on the Tobit regression model to explore the impact of green finance and environmental regulation on green innovation efficiency in this region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The intensity of environmental regulation and the degree of opening to the outside world will also inhibit urban green innovation. Lu et al [12] measured the development level of green intelligence in prefecture-level cities from 2005 to 2018 and explored both its temporal and its spatial evolution characteristics, and they used quantile regression tests and threshold regression to analyze its influencing factors and threshold effects. It was found that the level of opening to the outside world and the size of the city have a significant positive impact, while the level of economic development and the size of the government have a negative impact.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuing to deepen sustainable development, green and ecological benefits have become some of the main goals in the study of land use benefits. Land use is closely related to population growth, urbanization quality and environmental issues [13,14] and based on the connotation of land use benefit, some researchers quantified the green land use benefit of 284 cities at the provincial level and above in China based on green development goals, and pointed out that there are obvious spatial differences [15][16][17]. Studies from urban and rural land cover perspectives point out the differences in ecosystem functions between urban and rural areas [18], while the level of green land use has been evaluated from the perspective of the coupling coordination between land use and economic growth [19].…”
Section: Introductionmentioning
confidence: 99%